Strategi Komunikasi Penyuluh Agama Islam dalam Sosialisasi Penerapan Protokol Kesehatan Covid-19 Di Kota Medan - Wildan Ansori Hasibuan; Abdurrahman Abdurrahman; Mailin Mailin (PERSPEKTIF, 2022)
This study aims to analyze the communication strategy of Islamic religious educators in disseminating the application of the Covid-19 health protocol in Medan City, along with its effectiveness and communication barriers. This descriptive research uses interviews, observations and documentation studies as data collection techniques. The analytical knife used is the Diffusion of Innovation Theory, Uses and Gratification, and the theory of symbolic interactionism, and the Principles of Communication. The data is processed by data analysis techniques, the collected data is heard again, arranged systematically, read, analyzed, then identified answers and documents with research objectives, in order to obtain valid conclusions. The results of the study concluded that the extension strategy was carried out directly or face to face. At the time of the spread of Covid-19 at the end of 2019 the activities of religious instructors were divided into 2 methods, namely the first to continue to do it directly while still implementing the Covid-19 health protocol. Second, online or online using social media as a tool, by creating a special WhatsApp group for fellow Islamic religious instructors and majils ta'lim whose contents are appealing to health protocols and recording lectures that last 3-5 minutes. Technical barriers: Use of masks; washing with soap; Don't approach the crowd; Not traveling; Study at home; Pray at home; Body temperature detection and. Cough/sneeze etiquette. Political obstacles, blown by the opposition against the government.